Discourse of Islamic educational philosophy on Islamic educational psychology in Islamic education - Pranajaya, Syatria Adymas; Syamsul Rijal,; Fadlilah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The purpose of writing a discourse of the Islamic educational philosophy on Islamic educational psychology in Islamic education is to critically describe the discourse of these two scientific studies in the world of education. The method in this study is library research through library data relevant to educational philosophy, Islamic educational philosophy, and Islamic educational psychology. The analysis technique in this study is thematic analysis. The results of this study indicate that the Islamic educational philosophy towards the Islamic educational psychology is the core of educational philosophy that views education as a process of humanizing students as a person or a group of people who increase their human potential, so that they are able to develop and actualize themselves with all the original potential (fitrah) that exists in them psychologically. The values of fitrah have been attached to Islamic education, including that educators in educating their children must prioritize the philosophy of physical and psychological humanity, such as love (QS. Ali Imran: verse 31, QS. al-Hujaraat: verse 7, QS. at-Taubat: verse 103), compassion (QS. ar-Rum: verse 21, QS. Maryam: 96, QS. al-An’am: 12 and 54, QS. al-Hadid: 27), good teaching (QS. Al-Ahzab: 21, QS. An-Nahl: 125, QS. Al-Mujadalah: 11, QS. at-Taubah: 122), friendship (QS. Az-Zukhruf: 67, QS. Ali-Imran: 52 and 104), upholding justice (QS. Luqman: 17, QS. an-Nisa: 135, QS. An-Nahl: 76, QS. Al-Maidah: 8), always strive to obtain goodness (QS. al-A’raf: 56, QS. al-Isra’: 7, QS. al-Maidah: 100), so that in education there is two-way communication or even multi-directional interaction or transactions (QS. al-Baqarah: 133, QS. as-Saffat: 102).